Diagnóstico da reestruturação espacial e da dinâmica socioambiental provocadas pelo turismo na orla do Cumbuco - Caucaia-Ceará-Brasil - Mesquita, Ádamo de Figueiredo Nogueira (2014)
The present research, made through the coast of Caucaia in which there is Cumbuco beach as focus for the study, realizes a historical summary of the use and occupation of the area in question, exposing the conditioners not only environmental, but also economical and social of the locality. The flat coastal plains configure as one of the most fragile and vulnerable ecosystems to human occupation. With that, it is necessary that be made specific studies for its ordering, so it is done in a sustainable way. For that, the present work objected to analyze the socioenvironmental impact resulting from the use and occupation of Cumbuco beach, contributing effectively with suggestions to the adequate management of its coastal natural resources. This implies an adequate management of the coastal environment of Cumbuco's territory, which can come to prevent critical situations and propose guidelines compatible with the vulnerability of the region. In a specif way, the work makes a historical refreshment about the occupation in Cumbuco's surround, as well as identifies the vectors which led to spacial restructure of the community in question, analyses the tourism as valorization factor and spacial transformation of the coastal environment, and identifies the socioeconomic and environmental impact deriving from the touristic occupation and the new local activities. The method used is the qualitative-empirical with an investigative and exploratory approach, being done different field procedures during the research accomplishment period. These procedures assist in the updating regarding the new characteristics of the local infrastructure, as well as in the collecting of socioeconomic information and the analysis of the socioenvironmental impact. Eventually, it is concluded that with the reflex of determinations imposed by the new use forms and occupation of the region and the conservation of profitability (marks of touristic activity), beyond the exploration of natural environment, Cumbuco presents itself just as one more space chosen to be explored.